Knowledge Translation as Cultural and Epistemic Translation; Comment on "Sustaining Knowledge Translation Practices: A Critical Interpretative Synthesis" - John Ødemark (Kerman University of Medical Sciences, 2023)
This commentary examines the claim made by Borst et al that knowledge translation (KT) should look to Science and Technology Studies (STS), the sociology of translation, and constructionist views on knowledge, and begin to think of the sustainability of a certain practice as construction work in continuous progress, and not as states to be reached once and for all. While endorsing this claim, the present commentary also argues that what it calls the "epistemic reframing" behind the new construal of KT in Borst must be supplemented with approaches that goes beyond the sociology of translation. The commentary claims that this epistemic shift hinges upon a shift in the narrative framing of KT, and that we need to consider the broader narrative and historical ideology of knowledge dissemination behind KT, and that a failure to do so, leaves us with KT seen as a linear transmission of "true" knowledge to peoples and places lacking such knowledge.